Caracterização de milho crioulo e desfolha artificial de híbrido simples - Uitzil, Adán Marcel Puc (2017)
Corn is one of the cereals most important, being cultivated in several countries in the world, has a fundamental role in human food and animal, and being it also indispensable in industry. However, the tendency to overcome the productivity of this is a constant challenge. Thus, the objectives of the present study were: characterize families S1, S2 and S3 from landrace corn as to phenological development, thermal demand and flowering synchrony; reveal effects of artificial defoliation in philological maturity on yield components of corn hybrids, in different plant populations. The study 1 (E1) was carried at the farm harvest 2015/2016 in the experimental area of the Universidade Federal de Santa Maria, Campus of Frederico Westphalen (UFSM-FW). For this, 34 segregating families were studied in different generations, belonging to from four populations of landrace corn (Planalto, Dente de ouro, Argentino amarelo and Argentino branco). For this, five commercial hybrids were used as controls. For the study 2 (E2) were used two simple hybrids DKB 240 VT PRO® e DKB 290 VT PRO®). The experiment was carried in the municipality of Redemption/RS, in the harvest 2014/2015, in a randomized block design in a factorial 2x2x2 (hybrids, defoliation and plant population). In E1, the families AAS1F1, DOS3F3, ABS2F2, ABS3F1, PLS1F1, PLS3F1, PLS3F2 and PLS3F3 had flowering synchrony. The duration of vegetative stages of families was relative to the quantity of leaves developed. The families with the high number of leaves demanded high thermal requirement to reach the flowering, indicating that more time is needed to develop a high number of source-organs to maintain a higher biomass. For the E2, the total defoliation in the physiological maturity negatively affects the yield components of the ear, reducing ear length (5.6), the kernel mass per ear (10.9), the ear mass (8.9) and the grain yield (9.5%). The increase in plant population has reduced the number kernel per row (14.4), the kernel weight (22), the kernel mass per ear (21.3), the thousand kernel weight (10.6), the kernel length (3.8), the kernel width (3.9) and grain yield (9.5%). Artificial defoliation in physiological maturity and high plant populations negatively influenced the main components of maize production. The DKB 290 VT PRO® hybrid presents superiority on kernel mass per ear (6.9), ear length (16.3) and kernel length (4%) in relation to DKB 240 VT PRO® hybrid.